Investigation of effect of wall insulation thickness on window areas - Özel, Meral; Pihtili, Kâzim (My University, 2008)
In this study, effect of insulation thickness on glass area has been investigated numerically. For this purpose, glass area on the wall having different insulation thicknesses was increased from %0 to %100 with an ratio of %10 and, heat gain and losses according to be single glass and double glass of window were calculated. After calculations for all wall orientations had been repeated, results obtained were presented for summer and winter conditions as graphics. Consequently, it was seen that effect of insulation thickness on glass area was bigger in winter.
Duvar yalitim kalinli?inin pencere alanlarina etki?si? ni?n araştirilmasi
Keywords: Areas of windows; Building wall; Heat gain and loss; Insulation thickness